2005
DOI: 10.1007/s10950-005-8720-5
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and stress regimes in the Hellenic subduction zone from focal Mechanisms

Abstract: Fault plane solutions for earthquakes in the central Hellenic arc are analysed to determine the deformation and stress regimes in the Hellenic subduction zone in the vicinity of Crete. Fault mechanisms for earthquakes recorded by various networks or contained in global catalogues are collected. In addition, 34 fault plane solutions are determined for events recorded by our own local temporary network on central Crete in [2000][2001]. The entire data set of 264 source mechanisms is examined for types of faultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 53 publications
2
51
0
2
Order By: Relevance
“…Active quaternary normal faults known from geologic and sea-beam observations Armijo et al, 1992) are reported for these areas as well. The activation of these N-S to NNE-SSW trending normal faults is in agreement with the current stress field in eastern Crete (Bohnhoff et al, 2005) and consistent with fault-plane solutions indicating E-W extension in the region east of Crete (Fig. 1).…”
Section: Microseismicity Beneath Cretesupporting
confidence: 84%
See 1 more Smart Citation
“…Active quaternary normal faults known from geologic and sea-beam observations Armijo et al, 1992) are reported for these areas as well. The activation of these N-S to NNE-SSW trending normal faults is in agreement with the current stress field in eastern Crete (Bohnhoff et al, 2005) and consistent with fault-plane solutions indicating E-W extension in the region east of Crete (Fig. 1).…”
Section: Microseismicity Beneath Cretesupporting
confidence: 84%
“…However, we cannot exclude that this difference is caused by poor hypocentre precision of the historic events. Most of this shallow activity is likely to be caused by relative movements along transtensional structures caused by the oblique subduction and slab roll-back (Kahle et al, 2000; ten Veen and Kleinspehn, 2003;Bohnhoff et al, 2005). In the western offshore area, seismicity is generally confined to the plate interface with low seismic activity at the Ionian trench.…”
Section: Seismicity Of the Hszmentioning
confidence: 99%
“…Aegean (Hatzfeld et al, 1993;Friederich and Meier, 2008), on Crete (Bohnhoff et al, 2005;Jost et al, 2002;Meier et al, 2004;Becker et al, 2009), in the Cyclades (Bohnhoff et al, 2004;Dimitriadis et al, 2005Dimitriadis et al, , 2009 and in the western Hellenic subduction zone (Haslinger, 1998;Rigo et al, 1996;Papadimitriou et al, 2010). In view of the severe seismic hazard of the region, a central aim of all research efforts is and was to promote the understanding of the current seismotectonics of the Aegean.…”
Section: W Friederich Et Al: Focal Mechanisms and Stress Field In Tmentioning
confidence: 99%
“…Papazachos et al, 1991;Taymaz et al, 1991;Benetatos et al, 2004;Bohnhoff et al, 2005;Kiratzi et al, 2007), via observation of aftershocks which permit inferences on the size of the fault plane and the amount of slip (Drakatos and Latoussakis, 2001) and finally via stress field determinations from catalogues of focal mechanisms (Papazachos and Delibasis, 1969;Bohnhoff et al, 2005;Rontogianni et al, 2011). Besides seismicity, direct observations of plate motions by geodetic measurements (e.g.…”
Section: W Friederich Et Al: Focal Mechanisms and Stress Field In Tmentioning
confidence: 99%
“…It forms the plate boundary between the Anatolian plate in the south and the Eurasian plate in the north and slips at a rate of 20-30 mm=yr (McClusky et al, 2000). This kinematic framework is driven by the northward-pushing Arabian plate in the east and the southward-pulling rollback of the Hellenic subduction zone in the west (Flerit et al, 2004;Bohnhoff et al, 2005) (Fig. 1, right, bottom).…”
Section: Tectonic Setting and The Gonaf Projectmentioning
confidence: 99%